2002
DOI: 10.2527/2002.80123353x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-oil corn or added corn oil on ruminal biohydrogenation of fatty acids and conjugated linoleic acid formation in beef steers fed finishing diets

Abstract: Three Angus steers (410 kg) cannulated in the proximal duodenum were used in a replicated 3 x 3 Latin square to evaluate the effects of dietary lipid level and oil source on ruminal biohydrogenation and conjugated linoleic acid (CLA) outflow. Dietary treatments included: 1) typical corn (TC; 79.2% typical corn), 2) high-oil corn (HOC; 79.2% high-oil corn), and 3) the TC diet with corn oil added to supply an amount of lipid equal to the HOC diet (OIL; 76.9% TC + 2.4% corn oil). Duodenal samples were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
91
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(114 citation statements)
references
References 30 publications
13
91
1
9
Order By: Relevance
“…In ewes, duodenal flow of t10c12 CLA increased and c9t11 CLA decreased in response to graded increments of dietary concentrate with a constant level (7.4 g/100 g diet DM) of supplemental FA from soya-bean oil (Kucuk and Hess, 2004). Our results support the findings of others (Beaulieu et al, 2002;Duckett et al, 2002;Shingfield et al, 2005) that high concentrate diets support t10c12 CLA formation in the rumen. Replacing incremental portions of red clover with maize grain in dual-flow continuous cultures resulted in a linear increase in the output of t10c12 CLA into effluent (Latham et al, 1972).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In ewes, duodenal flow of t10c12 CLA increased and c9t11 CLA decreased in response to graded increments of dietary concentrate with a constant level (7.4 g/100 g diet DM) of supplemental FA from soya-bean oil (Kucuk and Hess, 2004). Our results support the findings of others (Beaulieu et al, 2002;Duckett et al, 2002;Shingfield et al, 2005) that high concentrate diets support t10c12 CLA formation in the rumen. Replacing incremental portions of red clover with maize grain in dual-flow continuous cultures resulted in a linear increase in the output of t10c12 CLA into effluent (Latham et al, 1972).…”
Section: Discussionsupporting
confidence: 88%
“…The decreased biohydrogenation of linoleic and linolenic acids with the LF diet suggested a lower biohydrogenation activity by cultures microbes. The low biohydrogenation values for oleic acid in this study compared with others (Duckett et al, 2002;Sackmann et al, 2003Kucuk andHess, 2004) may have resulted from the DHA effect on the reduction step in the biohydrogenation (AbuGhazaleh and Jenkins, 2004).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…FAs in plasma lipids extracts and in unextracted diet ingredients and milk samples were methylated using sodium methoxide followed by boron trifluoride as described by Park and Goins (1994). This method, which successively uses basic and acid transmethylations, allows methylation of all lipid classes, including non-esterified fatty acids, and does not alter the stereochemistry of CLA double-bonds (Duckett et al, 2002 For plasma analysis, flame ionisation detector temperature was maintained at 2608C and the injector at 2558C, and a splitless injection with an automatic injector was used. Helium was the carrier gas with a constant pressure (24.6 p.s.i.).…”
Section: Methodsmentioning
confidence: 99%
“…35) Many studies have reported that dietary supplementation with a linoleic acid-rich oil such as corn oil, 36) soybean oil 37) or safflower oil 38) increased the concentration of CLA in the ruminant. Similarly, in the present study using high-quality ESB, and the total CLA concentration in the body fat was significantly higher in the HTMT-treated and non-HTMT-treated dietary groups than in the control group.…”
Section: Discussionmentioning
confidence: 99%